Recasting and Validating a Search for Long Lived Particles using a CalRatio trigger in the ATLAS experiment - Coll Saravia, Lucía Ximena (2023)
The Standard Model (SM) of particle physics consists in a description of all the known elementary particles and their interactions. As far as it is known, the SM has passed all experimental tests, but presents some imperfections having no explanation for such as the presence of neutrino masses and the hierarchy problem. This encourages to probe theories beyond the Standard Model (BSM) that could bring solutions to these problems. An interesting proposal is to search for neutral long lived particles (LLPs). These type of particles have long decay lengths, can be generated by a variety of BSM models and could be detected in collider experiments by searching for displaced signals. The detection of the decay products of LLPs decays will contribute to the discovery of new physics. The objective of this work is to upgrade and optimize the PUCP Toy Detector presented in [1], adapting the simulation to the ATLAS detector and adding new features as a Geant4 simulation of the calorimeter for calculating the energy deposits. And validating it by reproducing the result of the searches presented in [2]. We conclude that the PUCP Toy Detector is valid, well implemented, and will be a competitive tool for searching new models containing LLPs decaying inside the calorimeters in the future.